The Effect of Arbuscular Mycorrhizal Tablets and Sachets on the growth of Pueraria javanica - Namrawati Ahmad; Muhammad Akhsan Akib; Sri Nurqadri; Syatrawati Syatrawati; Retno Prayudyaningsih (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2023)
Pueraria javanica (P. javanica) is a type of Leguminosae with a vine growth type with well-fixation nitrogen, so that can be used as a ground cover plant and forage food riched in protein (15-25%). In addition, the beneficial ability in symbiosis with arbuscular mycorrhizal fungi (AMF) has caused this plant to be utilized as the host plant for testing the effectiveness of different dosage forms of AMF on the growth of P. javanica which was carried out in Bukit Harapan sub-district, Parepare City at an altitude of 37.0 m asl with the coordinate point 3°59'30” S and 119°38'43” E. The study was conducted according to a randomized block design (RBD), AMF treatment dosage forms tested was powder (B1)/control, sachet (B2), and tablet (B3). The results showed that the form of AMF did not affect the effectiveness of stimulating the root length growth and volume, as well as the leaf number of P. javanica. AMF in tablet and sachet forms can enrich the AMF dosage form and can be a novelty for this field